O DISCURSO CONSERVADOR DO GOVERNO BOLSONARO À POLÍTICA DE DROGAS NO PAÍS ENQUANTO VIOLADOR DE DIREITOS HUMANOS: ENTRE FAKE NEWS, PRECONCEITOS E SAÚDE PÚBLICA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present essay seeks to investigate the Bolsonaro government’s conservative discourse on drug policy in the country as a human rights violator. With this, the scenario addressed is worked from the perspective of fake news, a mark of the current government, of public health and also of the prejudice rooted in repressive and selective discourses in national drug policy. For this, the article was subdivided into two main sections. It begins with the study of the called “war on drugs” and its relationship with the expansion of punitive power, proposing human rights as an essential phenomenon for thinking about drug policy contemporaneously. Continuing, the second chapter addresses the human rights violations promoted by the government of Jair Bolsonaro regarding the setback of the national drug policy, investigating elements that corroborate this reality, as is the case with fake news. Thus, the question arises: to what extent does the speech of the Bolsonaro’s government, responsible for a remarkable setback with regard to drug policy at the national level, violate human rights by raising its repressive conservatism? To solve the problem raised, the study uses the phenomenological-hermeneutic method, as a denial of the method as traditionally conceived, providing research with language as an event of Being. In the end, it is possible to infer that the conservative discourse of the federal government regarding drug policy violates human rights, on a large scale, as it does not consider the problem from the perspective of public health.